2023
DOI: 10.1136/ard-2023-223950
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prevalence and mortality of IgG4-related disease in the USA: a claims-based analysis of commercially insured adults

Abstract: BackgroundIgG4-related disease (IgG4-RD) is an immune-mediated condition that can affect nearly any organ or anatomic site. We sought to describe the epidemiology of IgG4-RD in the USA.MethodsWe used Optum’s deidentified Clinformatics Data Mart Database from 1 January 2009 to 31 December 2021 to identify IgG4-RD cases using a validated algorithm. We estimated the incidence rate and prevalence between 2015 and 2019 (when rates stabilised), standardised to the US population by age and sex. We compared mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In our study, the observed trend for increased total IgG4 concentration in week 3 for Vax patients may explain the reduced protective Ab responses. Of significance, clinical onset of IgG4-related non-infectious diseases is most often recorded in patients older than 50 years, which further corroborates our findings of increased mortality in this age group ( 16 , 17 ).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the observed trend for increased total IgG4 concentration in week 3 for Vax patients may explain the reduced protective Ab responses. Of significance, clinical onset of IgG4-related non-infectious diseases is most often recorded in patients older than 50 years, which further corroborates our findings of increased mortality in this age group ( 16 , 17 ).…”
Section: Discussionsupporting
confidence: 91%
“…The average age of diagnosis is the sixth decade of life, and it affects people of diverse racial and ethnic backgrounds. 3 The pathophysiology of this condition involves T-celldependent activation of circulating B-cells following an initial antigen trigger, resulting in a hypergammaglobulinemia with expansion of both B-cell plasmablasts and the oligoclonal IgG4 protein. 4,5 It is hypothesized that the increase in serum IgG4 in these patients is a sign of a failed counter-response to the original immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based estimates of IgG4-RD incidence and prevalence are limited. Using a claims-based algorithm to identify cases in the USA, the estimated incidence was 0.78–1.39 per 100 000 person-years between 2015 and 2019, and the point prevalence as of 1 January 2019 was 5.3 per 100 000 persons [ 3 , 4 ]. The incidence of pancreatic disease in Japan was estimated to be higher (3.1 per 100 000 persons) using different methods [ 5 ].…”
Section: Epidemiology Of Igg4-rdmentioning
confidence: 99%